STRATEGI BAURAN PEMASARAN DESA WISATA KAMPUNG EKOLOGI TEMAS DI KOTA BATU - Ninin Khoirunnisa; A. Yusuf Kholil (BUANA SAINS, 2018)
Marketing strategy is a plan that is done to be able to capture the market, using the 7 P Marketing Mix strategy. This study aims to 1) analyze internal and external factors in the development of the Kampung Ekologi Batu (KEB). 2) Analyzing the development strategy that must be implemented by the Kampung Ekologi Batu (KEB) in increasing tourist visits. 3) Analyzing the development strategy is the most effective way to increase tourist visits of the Kampung Ekologi Batu (KEB). The sample used in this study is divided into 2, namely: Purposive Sampling and Accidental Sampling. Pursposive Sampling consists of: Tourism Marketing Department at the Tourism Office, Head of Community Empowerment and Development of Temas Village, General Chair of Kampung Ekologi Batu (KEB), Chair of KEB Development, and Chair of Rw 06. Accidental Sampling taken by 30 visitors. The analysis used in this study used SWOT Analysis, IFE Matrix and EFE Matrix to produce IE Matrix strategies. The results of this study indicate that the Kampung Ekologi Batu (KEB) has used 7 P Marketing Mix (Product, price, place, promotion, People, Process and Physical Evidence) on the Internal KEB. The results of the IE Matrix obtained based on the weight and rating obtained from IFE and EFE indicate the position of the IE KEB Matrix in the Growing and Building area, which means that the business KEB is developing and has excellent potential to be able to increase tourism, and Analysis Results The most effective SWOT in the research is on the S-O strategy, namely: Improving service quality, package quality or products offered and maintaining the beauty and cleanliness of the Ecology Village and the beautiful environment.